Anal human papillomavirus genotype distribution and its associations with abnormal anal cytology among men who have sex with men - I Ketut Agus Somia; Tuti Parwati Merati; Dewi Dian Sukmawati; Ni Wayan Winarti; IGAA Elis Indira; Ida Bagus Dwija Putra; Made Yogi Oktavian Prasetia (Universa Medicina, 2022)
BACKGROUND Anal human papillomavirus (HPV) is associated with the severity of anal cytologic abnormalities that are precancerous lesions. Knowledge of HPV type distribution in populations at risk for anal cancer is needed. This study investigated anal HPV infections and cytological abnormalities among men who have sex with men (MSM). METHODS A cross-sectional study was conducted involving 90 men aged >30 years with a history of anal sexual intercourse with men. Demographic characteristics and sexual behaviors were collected by using a self-completed questionnaire. Anal cytological results were examined, and HPV genotyping was performed by the Linear Array HPV genotyping test. Descriptive analyses of subject characteristics, prevalence, and 95% confidence intervals (CI) were performed. A chi-square test was used to determine their associations with high-risk HPV infection and cytological abnormalities. RESULTS The overall prevalence of abnormal cytology was 32% (24/75), atypical squamous cells of undetermined significance (ASCUS) 17.33 % (13/75), 14.66% (11/75) were classified as low-grade SIL (LSIL) and no participant had high-grade SIL (HSIL). Prevalence of HPV infection with normal cytology was 86.27% (44/51), ASCUS 92.30% (12/13), and LSIL 100% (11/11). The most common types of anal HPV in participants with cytological abnormalities are HPV 16, HPV 18 for high-risk HPV, and HPV 11, HPV 6 for low-risk HPV. There were no associations between the predictor variables and the abnormal cytology (p>0.05). CONCLUSION There was a high prevalence of HPV infection in MSM with abnormal anal cytology. A routine anal Pap smear program and vaccination are needed to prevent HPV infection and anal dysplasia in MSM.